LITERATURE REVIEW: KAJIAN AKTIVITAS FARMAKOLOGI TUMBUHAN GALING (Cayratia trifolia L. Domin.) SEBAGAI AGEN IMUNOMODULATOR POTENSIAL - Y, Muhammad Ilyas; Badia, Esti; Jabbar, Asriullah; Halik, Halik; Nasrudin, Nasrudin; Malik, Fadhliyah; Salem, Sri Rahayu; Mubarak, Mubarak; Nurhikma, Nurhikma (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
The existence of an optimal immune system for humans is very important to fight infectious diseases that enter the body, which is called body immunity. Weak immunity affects the ability to fight various disease pathogens such as bacteria, viruses, functions, protozoa, and parasites that cause immunodeficiency conditions. Weak immune system function can be improved by administering immunomodulatory agents with immunostimulatory action. One of the plants with potential as an immunomodulator is galing (Cayratia trifolia L.). based on empirical studies and scientific studies of its biology and chemical content. This review aims to provide information on scientific data on various pharmacological activities of galing plants that support development as potential immunomodulatory agents in immunodeficiency diseases. In this review, primary data was collected online, in the form of national and international journals. The results of studies obtained from several journals and other sources can reveal the immunomodulatory potential of galing with flavonoids that have the ability to improve the immune system and alkaloid compounds that are immunostimulating, so they have the potential to be developed as natural immunomodulatory agents.